ESTIMATING THE ECONOMIC EFFICIENCY OF SUPPLEMEMTAL IRRIGATION IN RAINFALL AGRICULTURE - Salim Al-Niamy; Zeina Saadallah Al-Rawi (Mesopotamia Journal of Agriculture)
ABSTRACT According to its climate, Iraq is classified to be within the arid to semiarid region, supplemental irrigation was used on the rainfall irrigated fields including those in the governorate of Nineveh which represents the investigated area of the study. The conditions are worsened by the loss of irrigation water and the inefficiency of its usage, This is reflected in inefficient utilization of the available recourses including land, labour, capital, and supplemental irrigation water.The research attempts to estimate the economic efficiency and its two components(TE,AE), by relaying on the field data for a random sample which amounted to (53) farm . The estimations in the study were based on uses Data Envelopment Analysis(DEA) based on the variable of returns to scale .The farms using all production inputs(29 farms) showed that The technical efficiency for these farms reached (83%) which means that the farms should be able to produce the current level of wheat production using no more than (83%) of its input.And the Allocative Efficiency at(65%) meaning that the farmers should lower the production cost by decreasing the input by (35%),The jeneral of economic efficiency was about (59%)thus the farmers should use no more than (59%) of its input to produce the same level of its current production, in order to be economic efficient.